Projection of rainfall intensity-duration-frequency curves at ungauged location under climate change scenarios. (August 2022) - Noor, Muhammad; Ismail, Tarmizi; Shahid, Shamsuddin; Asaduzzaman, Md.; Dewan, Ashraf
Highlights: IDF curves at ungauged locations under climate change scenarios are estimated. The proposed framework can also project the IDF curves at ungauged locations. Satellite rainfall data is bias-corrected to estimate rainfall at ungauged sites. Change factor was estimated from GCM historical and future annual rainfall maximum. Uncertainty in the projected IDF curve was smaller for short-duration and vice-versa. Abstract: It is vital to quantify the changes in the IDF relationship due to climate change for designing climate-resilient urban hydraulic structures. Such projections are also important for ungauged locations due to the possible urban expansion or human settlements. This work proposed a method for IDF curve construction with associated uncertainty at ungauged locations under climate change scenarios, considering peninsular Malaysia as a case study. The bias in Global Satellite Mapping of Precipitation Gauge Calibrated (GSMaP_GC) data was estimated by comparing its IDF curve with the observed IDF curve. Daily rainfall simulations of four global climate models (GCMs), most suitable for the study area, were employed to approximate the possible alterations in future rainfall distribution for four radiative concentration pathways (RCPs). The results revealed changes in rainfall intensity by -3.4 − 26.7% during 2010−2039, -0.1 − 34.5% in 2040−2069 and -4.3 − 96.8% during 2070−2099 compared to base period 1971−2000 for different RCPs. Overall, the changes were pronounced for short-duration compared to high-duration rainfall. Also, higher emission scenarios showed a greater change than the lower scenarios. The climate change uncertainty range was wider for high-duration and smaller for short-duration. The uncertainty was also higher in the far future.